2004
DOI: 10.1038/sj.sc.3101662
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among people with high spinal cord injury living in the community

Abstract: Study Design: An exploratory, qualitative methodology. Objectives: To explore perceptions of quality of life (QOL) among community-dwelling people with high spinal cord injuries (SCI) and the factors they identified as contributing to, enabling or constraining the quality of their lives. Setting: Urban communities on Vancouver Island and in the lower mainland of British Columbia, Canada. Methods: Semi-structured interviews with both men (n ¼ 11) and women (n ¼ 4) with complete high SCI (C1-C4). Interpretive an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
110
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(122 citation statements)
references
References 72 publications
7
110
0
3
Order By: Relevance
“…53 In Canadian studies 12,101 finances were identified as constraints to the purchase of adapted vans or the pursuit of expensive leisure activities but not to attaining health-care or a meaningful every-day life: 'There's funds available [and] the technology's available to keep you mobile and healthy y[when] I did work I participated in support of the system and now that I need it, it's working for me'. 12 In both the US and Canada it was noted that the social environment could exert a negative impact on those with SCI, taking the form of bureaucratic 'red tape' 91 or 'power trips' 12 -'Freedom is still extremely limited. There's always somebody winding up to play a bit of a power trip somewhere' 12 -or overt stigma and discrimination: 'I see that barrier [of stigma] everywhere I goy 'You are different''.…”
Section: Nursingmentioning
confidence: 99%
See 4 more Smart Citations
“…53 In Canadian studies 12,101 finances were identified as constraints to the purchase of adapted vans or the pursuit of expensive leisure activities but not to attaining health-care or a meaningful every-day life: 'There's funds available [and] the technology's available to keep you mobile and healthy y[when] I did work I participated in support of the system and now that I need it, it's working for me'. 12 In both the US and Canada it was noted that the social environment could exert a negative impact on those with SCI, taking the form of bureaucratic 'red tape' 91 or 'power trips' 12 -'Freedom is still extremely limited. There's always somebody winding up to play a bit of a power trip somewhere' 12 -or overt stigma and discrimination: 'I see that barrier [of stigma] everywhere I goy 'You are different''.…”
Section: Nursingmentioning
confidence: 99%
“…For example: 'It became blindingly clear soon after the accident that I was the only one who could see me through this, that where I go in the future and what I do with my life was entirely up to me'; 73 'Quality of life is what you make it'; 69 'You can maintain a very high quality of life, just the same as beforeyIt's just however you want to limit yourself, [that] is the only thing stopping you'. 12 There was an apparent relationship between assuming responsibility and attaining control over one's own life. For example: 'You have to take control as much as you canyI direct my own care'.…”
Section: Nursingmentioning
confidence: 99%
See 3 more Smart Citations